THE INFLUENCE OF STRUCTURAL FE, AL AND MG ON THE INFRARED OH BANDS IN SPECTRA OF DIOTAHEDRAL SMECTITES - Bishop J.; Madejová J.; Komadel P.; Fröschl H. (My University, 2002)
Visible to near-infrared (NIR) reflectance spectra and mid-IR transmittance spectra are presented here for a collection of dioctahedral smectites. Analysis of the structural OH vibrations is performed by comparing the NIR combination and overtone bands with fundamental stretching and bending absorption features in the mid-IR region. Second derivatives are used to determine the actual band centres, which are often shifted slightly by a spectral continuum in the reflectance or transmittance spectra. New bands have been identified near 4170 and 4000 cm-1 in the NIR spectra of nontronite with tetrahedral substitution. A related band is observed near 4100 cm-1 for montmorillonites with substantial tetrahedral and/or octahedral substitution. These bands are correlated with the mid-IR bands near 680 cm-1 for nontronite and near 630 cm-1 for montmorillonite. Comparison of the OH overtone and combination bands with the fundamental stretching and bending vibrations gives consistent results.
Keywords: infrared spectroscopy; smectites; structural OH; montmorillonite; nontronite